Effect of Rat Pretreatment with Embryospecific Factors on the State of Liver Antioxidant System at Hypothermic Storage and Normothermic Reperfusion - Cherkashina, D. V.; Petrenko, A. Yu. (Problems of Cryobiology and Cryomedicine, 2003)
The effect of embryospecific factor pretreatment on liver oxidative-reducing balance after hypothermic storage (1 and 24 hours) in sucrose-saline solution, and normothermic reperfusion (60 minutes) has been studied. The decrease of free radical product number investigating by TBA-product level and accumulation rate, and normalization of antioxidant system enzyme activity (catalase, glutathione peroxidase and reductase) has been shown.